2021
DOI: 10.1007/s40964-021-00233-y
|View full text |Cite
|
Sign up to set email alerts
|

In situ alloying: investigation of the melt pool stability during powder bed fusion of metals using a laser beam in a novel experimental set-up

Abstract: The limited access to materials for the Powder Bed Fusion of Metals using a Laser Beam (PBF-LB/M) is compensated by in situ alloying. Individual melt pool characteristics can be specifically influenced to improve the mechanical properties of the final part. However, conventional PBF-LB/M machines allow only limited access for detailed observation of the process zone and, in particular, the melt pool. This paper presents a methodology for systematically analyzing the melt pool in the cross section to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The beam was expanded by a collimator (D50-F200, IPG, Burbach, Germany) and was then guided through the scanning system for area irradiation (intelliSCAN III30, Scanlab, München, Germany) and beam waist variation (varioSCAN de40i, Scanlab, München, Germany). A more detailed description of the test bench can be found in the work of [ 28 ]. The process monitoring system consisted of an off-axis thermographic camera (TC) and an off-axis high-speed camera (HSC2).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The beam was expanded by a collimator (D50-F200, IPG, Burbach, Germany) and was then guided through the scanning system for area irradiation (intelliSCAN III30, Scanlab, München, Germany) and beam waist variation (varioSCAN de40i, Scanlab, München, Germany). A more detailed description of the test bench can be found in the work of [ 28 ]. The process monitoring system consisted of an off-axis thermographic camera (TC) and an off-axis high-speed camera (HSC2).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The simulation model was validated with the experimental data of a single-track experiment using the novel test bench [10]. Following the usual practice, the geometrical information of the molten pool was used to quantify the accuracy of the simulation results on a global scale [21,38,39].…”
Section: Methodsmentioning
confidence: 99%
“…As the surface tension of AlSi10Mg is characterized by almost half the surface tension of 316L and is less sensitive to temperature variations [8,9], the Marangoni effects are significantly reduced with a high impact on the melt pool dynamics. Wimmer et al [10] showed an increasing melt pool stability with increasing Al content, which was attributed to the Marangoni convection.…”
Section: Introduction and State Of The Artmentioning
confidence: 96%